GP215 Growth and nutritional status in children with prader willi syndrome. (June 2019) - Meade, Christina; Martin, Ruth; McCrann, Ann; Lyons, Jacqueline; Roche, Edna
Abstract : Objective: To explore growth and nutritional status in children with Prader Willi Syndrome (PWS) Methods: All children with a genetically confirmed diagnosis of PWS, attending the National Children's Hospital Tallaght were invited to participate (n=44). Anthropometry, height/length, weight and body mass index (BMI) were measured were appropriate. Body composition was evaluated using bioelectrical impedance analysis. Parents completed a feeding questionnaire to identify early feeding issues in PWS. Parents received training on recording dietary intake before completing 3 Day Food Diaries to evaluate dietary intake. Nutritional bloods to assess iron and Vitamin D status were taken. Results: Participants included nineteen children. Median age was 7.9 years (range 0.6– 18.1 years). Majority were female (n=14, 74%). Median age at diagnosis was 2.5 weeks (range birth – 2.7 years). Growth Hormone treatment was in place for the majority (n=14, 74%) and commenced at a median age of 2.6 years. Of the reporting parents, 89% (n=17) were mothers with 37% (n=7) reporting to be homemakers. All children were living in 2 parent households. BMI was calculated for all children over 2 years (n=15). Using the BMI classification 20% (n=3) were underweight, 60% (n=9) were healthy weight, one patient was overweight and 13.3% (n=2) were obese. Body composition analysis was completed where appropriate (n=9), median% bodyfat was 26% and ranged from 10 - 40%. The majority reported early feeding issues, all of whom required admission to the special care baby unit with median length of stay of 7 days (IQR 14 days). Difficulties progressing with textures and difficulties achieving typical feeding milestones was reported in 7 cases (39%). Food seeking behaviours were present in 10 patients (55%) with a median age of onset of 3.7 years. Children achieved 41% - 112% of their estimated average requirement (EAR) for energy (median 82%, IQR 33). The macronutrient composition of the diet varied greatly. Insufficient micronutrient intake was reported for iron, calcium and vitamin D. Nutritional bloods identified iron deficiency anaemia and vitamin D insufficiency in 2 patients. 58% (n=11) were taking self-prescribed supplements. Conclusion: Early feeding issues are common in PWS. The majority of our cohort were classified as having a healthy BMI achieved through significant restriction of energy intake. Suboptimal dietary intake of and deficiencies in key nutrients was noted. This study highlights the importance of adjusting energy intake to prevent overweight and obesity while ensuring adequate micronutrient intake to support optimal growth and development.